FROM WAWQI TO INDIO, FROM QUECHUA TO SPANISH - Espino Relucé, Gonzalo (2008)
Hispanization in Andean countries is the result of a compulsory process. Although inclusionwas fostered among earlier patristic authorities, Spanish was preferred over theindigenous languages. In spite of laudatory praise of the vernacular, Spanish has beeninserted into the logic of the modernization process.